Translation Plays: La Malinche y otros intérpretes - Gladhart, Amalia (Latin American Theatre Review, 2018)
From the well-spoken Malinche, who translates Hernán Cortés’ semi-intelligible gibberish for a Spanish-speaking audience in Sabina Berman’s Águila o sol (1984), to the multilingual adolescents mediating between parents and host country in plays about immigration and exile, as in Roberto Cossa’s Gris de ausencia (1981), the translator is a frequent figure on the Latin American stage. Griselda Gambaro’s Es necesario entender un poco (1995) and Víctor Hugo Rascón Banda’s La mujer que cayó del cielo (1999) present complex representations of translation, showing it to be, at times, empowering and, at other times, limiting. Analyzing the above plays, this article considers why translation is performed in front of an audience or on the spectators’ behalf and how it may serve either to include or to exclude spectators or characters in the action of a given scene as well as highlight and question many of the constitutive elements of theatre. Interpretation ultimately ties translation and theatre together, as a translation is always an interpretation, just as interpretation is always part of theatre.